1989
DOI: 10.1002/ijc.2910430422
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a non‐tumorigenic human cervical keratinocyte cell line

Abstract: A human cervical keratinocyte cell line, W12, has been initiated from a low-grade cervical lesion histologically diagnosed as CIN I. This cell line has, to date, undergone over 300 generations in vitro with an average doubling time of 30 hr: an aneuploid karyotype has developed with progressive in vitro growth. W12 contains HPV16 DNA present at approximately 100 copies and the state of the viral DNA over a number of passages has been examined. The HPV16 DNA is stably maintained at high copy number over several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
237
0
3

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(243 citation statements)
references
References 22 publications
3
237
0
3
Order By: Relevance
“…We investigated the miRNA expression profile in normal cervical tissue and cervical carcinoma cell lines SiHa and CaSki containing integrated HPV-16 DNA. We also used two clonal derivatives, 20861 and 201402, of the W12 cell line derived from a low-grade cervical intraepithelial neoplasia grade I (CIN I) lesion (Stanley et al, 1989), which contain integrated HPV-16 DNA (Alazawi et al, 2002). Significance analysis of microarray (SAM) analysis of the array data showed that 24 miRNAs, including miR-126, -143, -145 and miR-195 (four of the ten most highly expressed miRNAs in the normal cervix) were underexpressed in all the integrated HPV-16 cervical cell lines compared to the normal cervix (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the miRNA expression profile in normal cervical tissue and cervical carcinoma cell lines SiHa and CaSki containing integrated HPV-16 DNA. We also used two clonal derivatives, 20861 and 201402, of the W12 cell line derived from a low-grade cervical intraepithelial neoplasia grade I (CIN I) lesion (Stanley et al, 1989), which contain integrated HPV-16 DNA (Alazawi et al, 2002). Significance analysis of microarray (SAM) analysis of the array data showed that 24 miRNAs, including miR-126, -143, -145 and miR-195 (four of the ten most highly expressed miRNAs in the normal cervix) were underexpressed in all the integrated HPV-16 cervical cell lines compared to the normal cervix (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Establishment of HPV-16 immortalized cell lines W12, V1/G and AC89/E2 has been described previously (Stanley et al, 1989;Bouvard et al, 1996;Storey et al, 1992). Keratinocyte cell lines were grown in a 3 : 1 mixture of DMEM and Ham F12 medium, supplemented with 10% foetal calf serum, 10 ng/mL epidermal growth factor, 10 710 M cholera toxin and 0.4 mg/ mL hydrocortisone at 378C and 10% CO 2 .…”
Section: Cell Culture and Genotoxic Treatmentmentioning
confidence: 99%
“…Little is known about the role of PTEN and LKB1 genes in (Dürst et al 1987a;Stanley et al 1989;Zheng et al 1994;Hietanen et al 1998). To establish an HPV-immortalized tonsillar epithelial cell line may provide a useful in vitro model to study HPV in tonsillar carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%